2007
DOI: 10.3748/wjg.v13.i5.676
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of glutathione S-transferase and matrix metalloproteinase-9 expressions are early events in esophageal carcinogenesis

Abstract: these alterations may be early events in carcinogenesis. Quantification of these parameters in Barrett's esophagus might be useful to identify patients at higher risk for progression to cancer. © 2007 The WJG Press. All rights reserved.Key words: Glutathione S-transferase; Matrix metallop ro t e i n a s e -9 ; B a r re tt 's m e t a p l a s i a ; E s o p h a g u s ; Adenocarcinoma; Dysplasia INTRODUCTIONEsophageal cancer is still one of the most widespread diseases, and the early diagnosis of esophageal carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 37 publications
4
40
0
5
Order By: Relevance
“…Another study found that MMP-1, -3, -7 and -10 along with TIMP-1 were increased along the sequence from BO to OAC [19]. MMP-9 demon-Picardo/Maher/O'Sullivan/Reynolds strates a similar trend [52], suggesting that alterations in these proteinases may be early events in oesophageal carcinogenesis. MMP-1, -3, -7 and -9 have been found to be prognostic biomarkers for oesophageal cancer [53].…”
Section: Role Of the Extracellular Matrixmentioning
confidence: 92%
“…Another study found that MMP-1, -3, -7 and -10 along with TIMP-1 were increased along the sequence from BO to OAC [19]. MMP-9 demon-Picardo/Maher/O'Sullivan/Reynolds strates a similar trend [52], suggesting that alterations in these proteinases may be early events in oesophageal carcinogenesis. MMP-1, -3, -7 and -9 have been found to be prognostic biomarkers for oesophageal cancer [53].…”
Section: Role Of the Extracellular Matrixmentioning
confidence: 92%
“…Higher level of MMP-1 expression has been associated with the lymph node metastases and possibly poor patient survival (89). Expression of MMP-9 is shown to be an early event during the EAC transformation and its expression levels are correlated with the progression of the disease (90)(91)(92). Activity of MMPs is inhibited by a family of proteins called tissue inhibitors of metalloproteinases (TIMP).…”
Section: Cancer-related Inflammationmentioning
confidence: 99%
“…It possesses proteolytic activity against type IV collagen, a major component of the BM, and has been shown to facilitate vascular smooth muscle cell migration [8]. The expression of MMP-9 is upregulated in a wide variety of human cancers [9,10]. MMP-9 expression is also significantly increased in CRC tissues [11].…”
Section: Introductionmentioning
confidence: 99%